Chronic Liver Disease in Ethiopia with a Particular Focus on the Etiological Spectrums: A Systematic Review and Meta-Analysis of Observational Studies - Behailu Terefe Tesfaye; Temesgen Mulugeta Feyissa; Azmeraw Bekele Workneh; Esayas Kebede Gudina; Mengist Awoke Yizengaw (Canadian Journal of Gastroenterology and Hepatology)
Background. In Ethiopia, chronic liver disease (CLD) is the 7th leading cause of death, accounting for about 24 deaths per 100000 populations in 2019. Despite its burden, there is a lack of compiled pieces of evidence on CLD in the country. Thus, this systematic review and meta-analysis is intended to provide the pooled estimates of CLD etiologies and mortality rate in CLD patients in Ethiopia. Method. PubMed, Google Scholar, ScienceDirect, institutional repositories, national digital library, and the bibliography of the eligible articles information were the source of data for the present review. The keywords “hepatitis, chronic” [Mesh], “end-Stage Liver Disease” [Mesh], “chronic liver disease”, “liver cirrhosis” [Mesh], and “Ethiopia” were used for the searches. Overall, we retrieved 199 records and 12 were included in this review. We used the DerSimonian-Laird random-effects models to perform the meta-analysis. We conducted subgroup and meta-regression analyses to account for the heterogeneity of the estimates. Result. Hepatitis B virus, alcohol, and hepatitis C virus are the three most common etiologies of CLD in Ethiopia accounting for a pooled estimate of 40.0% [95% CI: 29.0, 51.0, I2 = 96.3, p<0.001], 17.0% [95% CI: 9.0, 25.0, I2 = 96.7, p<0.001], and 15.0% [95% CI: 9.0, 21.0, I2 = 95.8, p<0.001], respectively. Unidentified etiology report has a substantial contribution accounting for an estimated pooled proportion of 45% [95% CI: 34.0, 56.0%, Q = 32.08, p<0.001, I2 = 87.53] of the CLD cases in the country. On the other hand, the overall hospital mortality rate in CLD patients is 25.0% [95% CI: 2.0, 47.0, I2 = 94.6, p<0.001] in Ethiopia. Conclusion. Hepatitis B virus, hepatitis C virus, and alcohol are the three most common contributors to CLD cases in Ethiopia. The authors warrant routine screening and strengthening of preventive and treatment programs for viral hepatitis B and C, further enhancing the alcohol policy of the country.